Dependencia en energía de la producción de picos de escape en espectroscopia de fluorescencia de rayos-X dispersiva en energía - Bravo Cabrejos, Jorge A. (2015)
A theoretical model is presented to calculate the energy and relative intensity of escape peaks corresponding to the characteristic X-rays present in an energy dispersive X-ray fluorescence (EDXRF) spectrum. The escape peaks of elements present in high concentration in a sample interfere with the identification of characteristic X-rays of elements present in low concentration. The results of this analysis have been used to simulate with good results the presence of the escape peaks in a sample of wood ashes with high concentration of K and Ca.